Quality Assurance Strategies in Medical Diagnostic Laboratories - Althobaiti, Sami Maqbul; Alammari, Fawaz Awadh; Alghamdi, Abdulaziz Ali Ahmed; Alghamdi, Mohammed Thakir Salem; Alkhammash, Yasir Mohammed Ahmed; Alghamdi, Abdulaziz Mohammed Hamdan (Journal of Posthumanism, 2024)
Medical diagnostic laboratories are foundational to modern healthcare, providing objective data that informs an estimated 70% of clinical decisions. The accuracy, reliability, and timeliness of laboratory results are therefore paramount to effective patient care and safety. However, the diagnostic process is vulnerable to error, with studies indicating that most individuals will experience a diagnostic error in their lifetime, contributing to significant patient harm, including tens of thousands of preventable deaths annually. To mitigate these risks, laboratories must implement a comprehensive Quality Management System (QMS). This paper provides a detailed analysis of the core strategies that constitute a robust QMS. It examines the foundational role of statistical quality control, including Internal Quality Control (IQC) for monitoring daily analytical precision and External Quality Assessment (EQA) for verifying inter-laboratory accuracy. The paper details the requirements of ISO 15189, the international standard for medical laboratory competence, emphasizing its holistic, process-oriented framework and its evolution toward proactive, patient-centered risk management. Furthermore, it explores strategies addressing human factors, such as structured staff training and competency assessment, and process control, including the development of Standard Operating Procedures (SOPs) and rigorous equipment maintenance. Finally, it discusses performance monitoring through quality indicators and audits. The central finding is that these strategies are interdependent and must be integrated into a cohesive system that extends across the entire total testing process. A commitment to this holistic approach is the fundamental mechanism by which laboratories can ensure diagnostic integrity, enhance patient safety, and fulfill their critical role in the healthcare ecosystem.